STUDENTS’ PERCEPTIONS OF SAVI (SOMATIC AUDITORY VISUAL INTELLECTUAL) METHOD IN IMPROVING ENGLISH SPEAKING SKILLS - Rina Asrini Bakri (Jurnal Pendidikan dan Pembelajaran, 2026)
Speaking is one of the most challenging skills in English language learning because students often experience low confidence, limited vocabulary, and fear of making mistakes during classroom interaction. This study aimed to explore students’ perceptions and learning experiences toward the implementation of SAVI (Somatic Auditory Visual Intellectual) method in English speaking learning at SMPN 3 Mare. This study employed a qualitative descriptive design involving 27 students consisting of 13 male students and 14 female students. Data were collected through classroom observations, semi-structured interviews, questionnaires, and document analysis. The findings revealed that students demonstrated positive responses toward the implementation of SAVI method because it created interactive, enjoyable, and collaborative classroom activities. Students reported that physical movement, visual materials, discussion activities, and problem-solving tasks helped them improve confidence and speaking participation. Female students generally showed stronger participation and communication confidence, while male students preferred practical and activity-based learning tasks. The study also found that SAVI method reduced students’ anxiety and increased classroom interaction during speaking activities. These findings suggest that SAVI method contributes positively to students’ speaking experiences and classroom engagement in English learning. Therefore, teachers are encouraged to implement interactive and student-centered strategies to improve speaking participation and learning motivation.